A STEP FORWARD IN THE FIGHT AGAINST ABLEISM: Damons v City of Cape Town [2022] ZACC 13 - Mabaso, Fanele (Obiter, 2023)
In Damons v City of Cape Town ([2022] ZACC 13) (CC judgment), the Constitutional Court (CC) had to deal with the issue of a person living with a disability who was injured in training. The minority judgment by Pillay AJ takes a socio-legal approach to the issue as it dives deep into how Mr Damons was injured and the responsibility of the employer to ensure that Mr Damons was reasonably accommodated. On the other hand, the decision of the majority by Majiedt J takes a formal legal approach in that it critiques the minority judgment from the perspective of the pleadings. This case note engages in a deep discussion of the matter, spanning the arbitration, Labour Court (LC), Labour Appeal Court (LAC) and both of the judgments of the CC. This case note engages in a discussion of the two judgments of the CC.